Improved Modleach By Using More Energetic Cluster Head Selection Technique - Saini, Manpreet; Singh, Sukhbeer; Chouhan, Neelam (International Journal of Computer Sciences and Engineering, 2019)
The cluster head selection of any clustering technique in Wireless sensor networks effects stability of a network and also makes that particular protocol more efficient. Many cluster head techniques in any cluster protocol like MODLEACH is based on probability and threshold but does not affect the network life if used in multihop concept. This paper, presents an energy efficient multi-hop of clustering approach in MOLEACH, where cluster heads are selected on the basis of remaining energy of sensor nodes and probability parameters. The node having the maximum energy will get more chance to act as a Cluster head. It increases the stability period of the network because cluster head needs more energy than normal nodes.